THE EFFECT OF PAYMENT ACCOUNTING INFORMATION SYSTEM ON THE EFFECTIVENESS OF INTERNAL CONTROL MITRA ANDAL SEJATI MEDAN - Minasari Nasution (Jurnal Ekonomi, 2022)
This study aims to determine the effect of the payroll accounting information system on the effectiveness of internal control at Mitra Andal Sejati Medan. The sample of this research was 70 employees of Mitra Andal Sejati Medan. Data analysis technique using Simple Linear Regression Analysis. The results showed that the value of the regression coefficient (b) of the payroll accounting information system was 0.771, which means that the better the payroll accounting information system, the more effective the internal control at Mitra Andal Sejati Medan is. The payroll accounting information system has a positive and significant effect on the effectiveness of internal control. The contribution of the payroll accounting information system to the effectiveness of internal control is 58.4%.